Identify Similarities and Differences between the IIA Standards and the Guide Work ofthe Internal Audit in Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This study aimed at an analytical comparison of the Internal Auditing Standards issued by the Institute of Internal Auditors (IIA) and the Guidance Manual for Audit Units issued by the Federal Audit Bureau to show the compatibility and differences between them and the possibility of applying the IIA standards to economic units in Iraq. The guideline was generally not covered by all the internal audit units. There is a lack of keeping pace with changes in internal auditing at the international level and there is a need to strengthen the Guideline on Internal Auditing Standards II A), which is characterized by the preparation of an internal document containing the objectives, powers and responsibilities of the internal audit work as well as the preparation of the program to ensure and improve the quality of part of the standards of qualities as well as the management of the internal audit activity and the preparation of the work plan and implementation and delivery of results and acceptance of risks and this included the performance standards, Internal Auditing Standards (IIA) in the work of internal audit units.Key terms of research: Internal Auditing Standards (IIA), Guiding Guide for Internal Audit Units